A systematic literature review on halal tourism policy in West Nusa Tenggara: Toward sustainable tourism development - Hendrawan Achmad Jofari; Riyanto Riyanto; Sarwono Sarwono (Goodwood Publishing, 2025)
Purpose: This study aims to evaluate the effectiveness of halal tourism policies in West Nusa Tenggara Province (NTB), Indonesia, as part of its strategic agenda to become a Muslim-friendly tourism destination. Methodology/approach: Using a Systematic Literature Review (SLR) of 32 scholarly articles published between 2021 and 2025, the study employs the CIPP evaluation framework (Context, Input, Process, Product) to analyze policy aspects. The review was conducted with halal tourism policies and how these policies contribute to sustainable tourism development. Results/findings: The findings reveal that NTB possesses strong geographical, cultural, and demographic advantages supporting halal tourism. However, challenges persist in human resource capacity, institutional coordination, and equitable distribution of outcomes. Policy formulation aligns well with both local and global demands, but implementation and monitoring require significant improvements. Conclusion: While NTB’s halal tourism policies have a solid foundation, enhancing execution and oversight is crucial for maximizing sustainable development benefits. Limitations: This study is limited by its reliance on secondary data from existing literature, which may not capture the most recent policy dynamics or on-the-ground realities. Contribution: The research contributes to public policy scholarship by providing a conceptual and evaluative synthesis of halal tourism policy effectiveness, highlighting areas for strategic improvement in Indonesia’s sustainable tourism development.